2020
DOI: 10.1007/s11239-019-02032-3
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient and outpatient treatment patterns of cancer-associated thrombosis in the United States

Abstract: Low molecular weight heparins (LMWHs) and direct oral anticoagulants (DOACs) are among the recommended treatment options for cancer-associated thrombosis (CAT) in the 2019 National Comprehensive Care Network guidelines. Little is known about the current utilization of DOACs in CAT patients, particularly on the inpatient to outpatient therapy transition. This study assessed real-world treatment patterns of CAT in hospital/ED in adult cancer patients (≥ 18 years) diagnosed with CAT during a hospital visit in IQV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…8 24 Although previous studies have shown that daily LMWH self-injections are well accepted by patients with CAT, our findings indicated the treating physicians experience a growing expectation from patients to choose a DOAC, supporting previous observations that patients with cancer generally prefer orally administered drugs if they are equally effective. 25 26 27 28 29 In a complex clinical situation as CAT, patients' needs and preferences are diverse, and incorporating the patients' attitude regarding the anticoagulant treatment is essential. 30 Concordant, many of the free-text responses indicated that treating physicians in this survey included patient preferences when weighing treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…8 24 Although previous studies have shown that daily LMWH self-injections are well accepted by patients with CAT, our findings indicated the treating physicians experience a growing expectation from patients to choose a DOAC, supporting previous observations that patients with cancer generally prefer orally administered drugs if they are equally effective. 25 26 27 28 29 In a complex clinical situation as CAT, patients' needs and preferences are diverse, and incorporating the patients' attitude regarding the anticoagulant treatment is essential. 30 Concordant, many of the free-text responses indicated that treating physicians in this survey included patient preferences when weighing treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…DOACs were the most common initial post-discharge outpatient option. Persistence and adherence in outpatients appeared higher in patients using DOACs or warfarin versus LMWH or UFH [ 8 ]. In another retrospective cohort study, from 2000 through 2003, warfarin ± injectable was used in approximately 90% of cases.…”
Section: Overviewmentioning
confidence: 99%
“…The real world data from one the registries shows that LMWHs were the most common initial anticoagulation for CAT (25). In this review, the authors reviewed four sizeable real-world data sets for type of anticoagulation therapy for the initial and ongoing management of CAT (25)(26)(27)(28)(29). The two most extensive series included in this review included 8,125 and 14,086 patients, respectively.…”
Section: Real World Data For Doacs Use In Gi Cancersmentioning
confidence: 99%